Prognosis of abnormal uterine bleeding in women of reproductive age with extragenital disorders - Blagoveshchensky, Roman; Tuchkina, Iryna (ScienceRise: Medical Science, 2023)
The purpose of the study was to elaborate on a prognostic model for predicting the development of abnormal uterine bleeding in women of reproductive age with accompanying extragenital disorders based on mathematical methods. Materials and methods. The study, which was in 2019-2022, involved 100 women of reproductive age with AUB and accompanying extragenital disorders under observation, who made up the main group. The control group comprised 50 women of reproductive age undergoing medical checkups. On the basis of 23 diagnostic indicators, the most informative ones were mathematically selected for the prognosis of AUB in women with extragenital abnormalities. Results and their discussion. The prognosis of the risk of developing AUB in women of reproductive age with extragenital disorders was carried out on a double scale (0 – low probability, 1 – high probability). The search for diagnostically informative factors involved a set of 23 working indicators that were investigated in the examined patients using four levels of the risk scale. In order to solve this issue, the factors that have the greatest importance in the formation of the prognosis were selected using discriminant analysis methods, and a corresponding mathematical model was created. The classification functions made it possible to enter the practical plane and form rules for assessing the presence/absence of the risk of developing AUB in patients of reproductive age with extragenital disorders. The corresponding expressions are the following equations: NP = BAS ART*75.57+FSH*2.96+prolac*0.02+estrad*0.02-40.78 PP = BAS ART*105.35+FSH*0.79+prolac*0.1+estrad*0.08-114.49, where NP is a negative prognosis, PP is a positive prognosis. If NP > PP, then the most likely prognosis is the absence of AUB in the patient; otherwise, if PP > NP – there is an increased risk of AUB. Conclusion. Pulsation index in the basal arteries of the uterus, FSH, prolactin and estrogens are prognostically significant indicators for predicting the risk of abnormal uterine bleeding in patients of reproductive age with extragenital disorders. The above formula, obtained from the conducted discriminant analysis, makes it possible to predict bleeding in a specific patient